Late sowing of cover crops reduces potential for nitrate leaching reduction and carbon inputs - Kumar, Uttam; Engedal, Tine; Hansen, Veronika; Gislum, René; Munkholm, Lars J.; Thomsen, Ingrid K.; Larsen, Søren Ugilt; Hansen, Elly Møller (Agriculture, ecosystems & environment, 2025)
Good establishment of cover crops early after harvest of the main crop is challenging and requires optimized sowing time to maximize ecosystem services in Northwestern Europe. We quantified the abilities of three cover crop species, fodder radish (Raphanus sativus), oats (Avena sativa), and phacelia (Phacelia tanacetifolia) to (i) take up nitrogen (N), reduce nitrate leaching when sown at four sowing times from 10 Aug to 7 Sep at two sandy loam sites in Denmark (Foulum and Flakkebjerg) during two percolation periods of 2022–23 and 2023–24, and (ii) provide carbon (C) input to the soil at two sowing times at Flakkebjerg in 2023. N uptake and nitrate leaching reduction declined with delayed sowing time. The decline followed different patterns for N uptake and nitrate leaching reduction and varied depending on interactions between species, percolation period, and site. Each day of delayed sowing from 10 Aug to 7 Sep decreased the ability of cover crops to reduce nitrate leaching by 0.5 kg N ha⁻¹ day⁻¹ at Flakkebjerg and 1.2 kg N ha⁻¹ day⁻¹ at Foulum. Overall, fodder radish and phacelia more efficiently reduced leaching at the early sowing times, while fodder radish was most effective at the later sowing times. At Flakkebjerg in 2023, fodder radish accumulated more C than oats and phacelia when sown on 10 Aug. Delaying sowing to 30 Aug reduced total C input from all cover crops by 60 %. These findings can potentially be used for enhancing environmental and climate benefits of cover crops in sustainable cropping system design. •N uptake, nitrate leaching reduction, and C input declined with late sowing.•Decline was dependent on sowing time, species, year, and site and their interactions.•The decline was higher on the site with sandier soil and higher precipitation.•Early sowing of fodder radish effectively maximized cover crop benefits.